Interaction Patterns of Teachers and Students in the Perspective of Surah Al - Kahf Verses 60-82 and Their Application in the Context of Today's Education - Muhammad Miftah Fauzan; Lilis Karyawati; Nia Karnia (al-Afkar, Journal For Islamic Studies, 2025)
The background to this problem is that the education carried out by teachers only emphasizes the transfer of knowledge, not the formation of attitudes and behavior. Therefore, researchers see a lack of interaction between teachers and students in the learning process. So researchers are interested in examining the interaction patterns between teachers and students contained in Surah al-Kahf verses 60-82. The formulation of the problem in this research is what the pattern of interaction between teacher (Khidir) and student (Musa) is in Q.S al-Kahf verses 60-82. The aim of this research is to find out the pattern of interaction between Prophet Khidir and Prophet Musa in Q.S al-Kahf verses 60-82. This type of research is library research. The data collection technique is a library technique by analyzing and collecting data related to the discussion as well as some literature regarding interaction patterns contained in Q.S al-Kahf verse 6 60-82. The object of the research is to explore based on the Tafsir book and relevant books. The data analysis technique uses content analysis to explore the content of Surah al-Kahf verses 60-82. The results of this research show that the interaction pattern between the teacher (Khidir) and the student (Musa) uses a two-way interaction pattern, namely that the teacher and student both play an active role in the learning process. This pattern uses a question and answer method. After the teacher explains the material, the teacher will give students the opportunity to ask questions and then be answered by the teacher. The teacher poses problems to the students so that it can give rise to student initiative to solve the problem which causes interaction between the teacher and students so that the student's role is active. In this story there are educational components, namely educational goals, educators, students, materials and methods related to interactions in today's education.